The pragmatic goal-based approach to ESP teaching with «Why» as the leading aspect - Zinder, E.Z.; Yunatova, I.G. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The article suggests a goal-based approach to teaching effective methods of dealing with professional English-language materials in dynamic, integrated, and fast developing disciplines like Information and Communication Technology and Enterprise Architecture. The main leading aspect of the approach is «Why» — aspect which determines the learner’s goals, and it is shown how the methods comprising the discussed approach are subordinate to those goals. The authors suggest replacing isolated learning English for Specific Purposes (ESP) with studying professional materials in English in close collaboration with subject experts and on their request. Educational methods including teaching effective reading, written summarising, and developing learner autonomy are described, and results of practical utilizing the approach is presented.
«Неге» жетекші аспектісі бар ESP оқытудағы мақсаттарға негізделген прагматикалық тəсіл
Основанный на целях прагматичный подход к обучению ESP с ведущим аспектом «Зачем»
Keywords: English for specific purposes; goal-based approach; effective reading; summarising; annotating; Academic English; learner autonomy; cognitive challenge